Learning Transformation Based on Literacy, Numeracy, and Technology Adaptation (Case Study of the Implementation of the Batch 6 Teaching Campus Teaching Program) - Yulia Savika Rahmi; Ahmad Saefudin (Institut Agama Islam Negeri Imam Bonjol Padang, 2024)
This study aims to examine the improvement of literacy, numeracy, and technological adaptation skills through the Campus Teaching Program at SDN 3 Buwaran Mayong Jepara. The method used in this research is a descriptive qualitative research approach with a case study design. The research subjects are SDN 3 Buwaran Mayong Jepara, focusing on analyzing reading, writing, arithmetic skills, and technological adaptation. Instruments used for data collection include observation, interviews, and documentation. This research implies the importance of implementing more intensive and sustainable mentoring programs in literacy, numeracy, and technological adaptation at SDN 3 Buwaran. Practically, the findings of this research emphasize the need for collaboration between schools, the Campus Teaching Program, and other stakeholders to enhance teachers' pedagogical skills through training and mentoring. Additionally, the results highlight the importance of using teaching modules and lesson plans that focus on improving students' basic skills, including literacy, numeracy, and the use of technology in teaching. Thus, school policies should be directed towards developing programs that support overall improvement in learning quality.